Estimación del Carbono Derivado de la Materia Orgánica en el Páramo de la Comunidad Cumbijín, del Cantón Salcedo, Provincia de Cotopaxi, periodo abril - agosto 2019. - Jiménez Rea, Leticia Elizabeth (2019)
The carbon content derived from organic matter in the soil is an important indicator of the capture balance - CO2 emissions globally. In the present study, the organic carbon content in the soil of the moor of the community of Cumbijín (40.7 km2) was estimated. The study consisted of three stages, which were field sampling, laboratory analysis, and geostatistical analysis. The carbon content in the soil of the moor, was obtained from 20 samples, which were subjected to the calcination method proposed by Walkley & Black (1934), to obtain the percentage of organic matter (MO) and the ratio that exists with the percentage organic carbon, using the Van Bemmelen conversion factor (1.72). These data were interpolated from the KRIGIN method. The investigation resulted in percentage ranges of 4.39- up to 20.88 % of the CO with respect to the total soil weight, with an average of 12.33 % percent. Finally, from the calculation of the apparent density, an average of 2.47 ton / ha at 30cm depth was obtained, these data reflect that there are relatively high concentrations in relation to other types of soils.